KIM AS ENABLER OF AROS TOURISM DESTINATION DEVELOPMENT (CASE STUDY OF KIM GATMEDIA GUNUNG ANYAR TAMBAK SURABAYA) - Manik Sunuantari (Jurnal Ilmiah Ilmu Komunikasi Communique, 2021)
Gatmedia Community Information Group (Kelompok Informasi Masyarakat Gatmedia/KIM Gatmedia) is a partner of the Surabaya City Government who was act as an entity enabler in developing AROS Tourism Destination at Surabaya. KIM’s role such as empowering community in disseminating information for various innovations and marketing programs in digital media. This study aims to study in depth on the impact of KIM Gatmedia for their community in managing AROS (Amazing River of Surabaya) green tourism. The theory used is tourism enabler. The method used is a case study, by selecting the research location of the mangrove tourist area of Gunung Anyar Tambak Surabaya. The results showed that KIM Gatmedia gave a significant impact for the community in the social, cultural, and economic through their communication activities for tourism branding.